QTL and candidate gene analyses of rootstock-mediated tomato fruit yield and quality traits under low iron stress - Asins, María J.; Raga, Verónica; Torrent, D.; Roca, Dolors; Carbonell, Emilio A. (R.G.F. Visser, Laboratory of Plant Breeding, 2020)
The use of iron-efficient rootstocks can be a sustainable way to enhance iron (Fe) fruit content in tomato. A hybrid tomato variety was grafted on a genotyped population of recombinant inbred lines derived from Solanum pimpinellifolium, and compared with self- and non-grafted controls under low iron (5.2 µM) growing conditions. Rootstock effects on total fruit yield, fruit [Fe] and yield Fe content (FeUEc) were the target traits; other minerals were also investigated by quantitative trait loci (QTL) and candidate gene analyses. The rootstock genotype affected fruit concentrations of Fe, Ca, Mg, Mn, Na, P, S, Si and Al. Most rootstocks increased FeUEc. Fruit and leaf [Fe] and FeUEc were genetically complex, involving epistatic interactions. Six and eight QTLs were detected for these traits, respectively, by multiple QTL mapping. Two kinds of relevant genes were found among candidates within QTLs for iron related traits: those coding for secretory proteins specific of the tomato xylem sap under iron deficiency, and others having a role in iron uptake such as TOMLHA1, FRO1, NRAMP2, FER and MYB72. Detected QTLs might reflect differences in the regulatory regions of those relevant genes, more than in their coding sequences.